Predicting the Influence of Digital Leadership on Performance of Private Higher Education Institutions: Evidence from Malaysia - Lim, Chang Hong; Teoh, Ai Ping (Journal of Entrepreneurship, Business and Economics, 2021)
This paper aims to investigate the impact of digital leadership on the institutional performance of private higher education institutions (PHEIs) in the digital era. Supported by the Resource-Based View Theory and the digital leadership dimensions based on the International Society for Technology in Education-Administrators (ISTE-A) standards, the study examined the roles of visionary leadership, digital-age learning culture, professional excellence, systemic improvement, and digital citizenship influencing the performance of PHEIs in Malaysia. An online questionnaire survey was adopted, and a non-probability sampling method utilizing purposive sampling was applied.  A total of 121 usable responses were collected from leaders in Malaysia PHEIs and analyzed based on structural equation modelling via the SmartPLS 3.3. The results showed that digital-age learning culture, professional excellence, and digital citizenship positively affect the PHEIs performance. However, visionary leadership and systemic improvement do not have a significant positive relationship with performance. The findings provide information to future researchers and leaders in PHEIs on the vital roles of a digital-age learning culture, professional excellence and digital citizenship in today’s institutions. The novelty of this study contributed to the body of knowledge in digital leadership and performance in the context of PHEIs in an emerging market. Research paper Keywords: Digital Leadership; Learning Culture; Professional Excellence; Digital Citizenship; Higher Education Institutions; Performance Reference to this paper should be made as follows: Lim, C. H., & Teoh, A. P. (2022). Predicting the Influence of Digital Leadership on Performance of Private Higher Education Institutions: Evidence from Malaysia. Journal of Entrepreneurship, Business and Economics , 10 (1), 1–38.